The perception of active listening practice on social networks - Pina, Lídia Silveira (2018)
Pina, L. S., Loureiro, S. M. C., Rita, P., Sarmento, E. M., Bilro, R. G., & Guerreiro, J. (2018). The perception of active listening practice on social networks. In 2018 Global Marketing Conference at Tokyo Proceedings (Vol. 2018, pp. 1098-1106). Global Alliance of Marketing & Management Associations. DOI: 10.15444/GMC2018